Complex Surgical Management of Radiation-Associated Left Retroperitoneal Sarcoma. Issue 9 (September 2022) - Walker, Jasmine C.; Bradley, Joel F.; Luckenbaugh, Amy N.; Lambright, Eric S.; Sandvall, Brinkley K.; Keedy, Vicki L.; Holt, Ginger E.; Tan, Marcus C. B.
Radiation-associated sarcomas (RASs) are rare entities that tend to have an aggressive course and poor prognosis. Criteria for diagnosis of radiation-associated sarcoma include therapeutic radiation preceding the development of sarcoma, sarcoma arising within or near the irradiated field, and tumor histology that is distinct from the primary tumor necessitating radiation. Despite their relatively uncommon occurrence, RASs are a well-established complication of radiation therapy. We present the complex, multidisciplinary surgical management of a patient with multi-compartmental radiation-associated sarcoma of the left retroperitoneum occurring nearly 25 years after undergoing whole trunk radiation for Hodgkin's lymphoma.